Water management technologies for sustainable agriculture in Kenya - Blank, Herbert G., author; Ngigi, Stephen N., author; Sijali, I. V., author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2007)
Improving food production in Kenya, as well as elsewhere in sub-Saharan Africa (SSA), is a daunting problem. Agricultural production is generally low, averaging less than one ton per hectare, which translates to a continuing cycle of poverty for millions of smallholder farmers. Improved utilization of water resources for agricultural production is an important prerequisite for increasing food production and incomes. This paper reports on experiences with a number of water management technologies and approaches in Kenya that are leading to sustainable increases in agricultural production and increased employment and incomes for smallholder farmers. Among these improvements are rainwater harvesting, improved performance of smallholder irrigation schemes, micro-irrigation technologies, and the participation of smallholders in export-oriented vegetable and other high-value crops production. Farmers who have access to seasonal water runoff can improve production with rainwater harvesting technologies. Modest investments and technical support have measurably improved the performance of existing smallholder schemes in Kenya. Micro-irrigation technologies, such as treadle pumps and low head drip kits, have provided farmers with low-cost methods of improving water management and agricultural production. Smallholder farmers throughout Kenya are participating as outgrowers in the production of export-oriented crops, meeting international quality and safety standards and substantially increasing incomes. The paper discusses these promising technologies and highlights recent research and interventions.
USCID fourth international conference
Not digitized by CSUL Digital Services.
Presented at the Role of irrigation and drainage in a sustainable future: USCID fourth international conference on irrigation and drainage on October 3-6, 2007 in Sacramento, California.